Flares at Earth and Mars: An Ionospheric Escape Mechanism?. Issue 8 (18th August 2018) - Mendillo, M.; Erickson, P. J.; Zhang, S.‐R.; Mayyasi, M.; Narvaez, C.; Thiemann, E.; Chamberlain, P.; Andersson, L.; Peterson, W.
Abstract: Solar flares are nature's active experiment upon a planet's upper atmosphere and ionosphere. Observed effects at Earth are consistent with a "second sunrise" scenario that produces changes in electron density, electron temperature, and plasma dynamics. A solar active region in September 2017 provoked ionospheric disturbances due to solar flares observed at Earth (6 September) and later at Mars (10 and 17 September). Incoherent scatter radar observations from the Millstone Hill Observatory showed a burst of upward diffusion due to electron temperature enhancements. We explore the companion possibility of flares causing upward drifts and plasma escape at Mars. Solar observations made by the EUV Monitor instrument on the Mars Atmosphere and Volatile EvolutioN (MAVEN) satellite are used to portray the time histories of irradiance changes to determine the "early" (onset to peak emission) and "late" (decay to background) time scales for these flares. During the initial phase of a flare (when photons ionize an atmosphere unmodified by flare heating), MAVEN was well above the ionosphere and thus no in situ data are available to asses this period of possible plasma escape. Estimates made using a simple terrestrial model for plasma drifts in the topside ionosphere suggest that escape rates can be enhanced at Mars at "early" times. The "late time" effects observed below 400 km 2 hr after the flare onset times did not reveal conclusive remnants of the proposed mechanism. No model of the Martian thermosphere‐ionosphere system has produced a self‐consistent simulation of solar flare effects upon Mars' upper atmosphere and ionosphere. Key Points: Observations and models for Earth show that flare‐induced ionospheric enhancements of N e and T e lead quickly to plasma escape September 2017 flares confirm terrestrial pattern at early times (~10 min), but observations at Mars only available after ~2 hr For Mars, analytical 1‐D model predicts upward plasma drift capable of escape; new observations for "early time" flare effects needed